Adolescência e suas marcas: o corpo em questão - Beatriz Akemi Takeiti; Cristiana Carneiro; Simone Ouvinha Peres (Desidades, 2021)
This article aims to reflect on the importance of the body theme in studies addressing adolescence and youth. The body is present in the polis not only in the scenario of current care and assistance public policies, but also as a contribution to future investments. In addition, there is the expressive body that, through its marks, provides us with a symbolic field beyond its biological dimension. Finally, there is the body that problematizes the delimitation of the adolescence and youth categories, indicating the multidimensionality of its understanding.